Minsky, monetary policy, and mint street: Challenges for the art of monetary policymaking in emerging economies - Srinivas Yanamandra (Levy Economics Institute of Bard College, 2014)
This paper examines the emerging challenges to the art of monetary policymaking using the case study of the Reserve Bank of India (RBI) in light of developments in the Indian economy during the last decade (2003-04 to 2013-14). The paper uses Hyman P. Minsky's financial instability hypothesis as the conceptual framework for evaluating the endogenous nature of financial instability and its potential impact on monetary policymaking, and addresses the need to pursue regulatory policy as a tool that is complementary to monetary policy in light of the agenda of reforms put forward by Minsky. It further reviews the extensions to the Minskyan hypothesis in the areas of setting fiscal policy, managing cross-border capital flows, and developing financial institutional infrastructure. The lessons learned from the interplay of policy choices in these areas and their impact on monetary policymaking at the RBI are presented.
Keywords: E58; G01; G28; 330; Financial Crisis; Central Bank; Monetary Policy; Bank Regulation; Fiscal Policy; Exchange Rate Policy; Financial Institution Infrastructure